Etiology and Clinical Pattern of Patients Presenting With Pancytopenia at Tertiary Care Hospital (Medical Forum Monthly, 2024)
Objective: The objective of the study was to evaluate the various cause and clinical presentation in patients having pancytopenia in tertiary care hospital.Study Design: Descriptive / cross-sectionalPlace and Duration of Study: This study was conducted in the Medicine Department of LUMHS, Jamshoro from 2013-2015.Materials and Methods: Total 80 cases of pancytopenia were enrolled in the study. Patients were included above age of 15 years from both sexes. Pancytopenia was defined as: WBCs (≤4.0×109/L), hemoglobin (≤10.0 g/dl) as well as platelet counts (≤150×109/L). All the clinical features and etiological pattern were noted in all cases and entered in the proforma. All the information was entered on SPSS version 18 and was analyzed.Results: Total 80 cases were studied, who represented pancytopenia. Male were in majority 61(76.25%). Majority of the young cases was found with mean age of 33.23 years. Most common clinical feature was found general weakness in 19(23.75%) patients followed by fever (18.75%), dyspnea 11(13.75%), bone pain 6(7.5%), anemia 6(7.5%) and pain in legs in 4(5%) patients. According to the etiological pattern aplastic anemia and malaria was found most common in 18 (22.5%) and 11 (13.75%) cases respectively.Conclusion: Aplastic anemia and malaria was the commonest factor of pancytopenia in this study mostly in young males. The commonest clinical presentation observed was generalized weakness after that fever and dyspnea.